2012
DOI: 10.1007/s11434-012-5156-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of a toxic dinoflagellate Alexandrium catenella DH01: Detection and identification of cell surface proteins using fluorescent labeling

Abstract: Alexandrium catenella DH01 is a toxic dinoflagellate species that is able to not only produce paralytic shellfish toxins, but also cause harmful algal blooms along the coast of China. In this study, we presented a new protocol for specific labeling and detection of the cell surface proteins (CSPs) of A. catenella DH01 cells using CyDye difference gel electrophoresis (DIGE) fluor minimal dyes. CSPs were identified using two-dimensional gel electrophoresis (2-DE) and MALDI TOF-TOF mass spectrometry (MS). The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In addition, RNA and DNA can be extracted simultaneously from the same sample for further analysis. This method has been widely applied in many dinoflagellate species, such as planktonic P. donghaiense [120], PSP toxin-producing A. catenella [121,122,123,124], and YTX-producing Lingulodinium polyedrum [125]. Nevertheless, a few reports have suggested that this method may not produce high-quality results for certain dinoflagellate samples.…”
Section: Application Of Molecular Tools For Studying the Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, RNA and DNA can be extracted simultaneously from the same sample for further analysis. This method has been widely applied in many dinoflagellate species, such as planktonic P. donghaiense [120], PSP toxin-producing A. catenella [121,122,123,124], and YTX-producing Lingulodinium polyedrum [125]. Nevertheless, a few reports have suggested that this method may not produce high-quality results for certain dinoflagellate samples.…”
Section: Application Of Molecular Tools For Studying the Mechanismmentioning
confidence: 99%
“…Most proteomic studies in the area of algal toxins have focused on PSP toxin biosynthesis in Alexandrium spp. [118,122,123,124,128,129,130,131]. Certain researchers have compared the 2-DE profiles of 2 strains with considerable variations in the levels of toxins triggered by different environmental conditions or growth phases [124,129,130].…”
Section: Application Of Molecular Tools For Studying the Mechanismmentioning
confidence: 99%
“…Dinoflagellates are differentiated from one another by the pattern of thecate or amphiesma which is made up of cellulose plates that protect the cells from the tugor pressure [1,3]. Previous study on the fossils of ancient dinoflagellates revealed six patterns of plate that classified the species into different major groups; gymnodinoid, suessioid, peridinioid, gonyaulacoid, dinophysoid, and prorocentroid [4].…”
Section: Dinoflagellates: Multifaceted Microorganismsmentioning
confidence: 99%
“…This topic contains 12 papers produced by research groups from China, Germany, and Korea. To help readers, we have arranged the papers according to their research topics: genomics [1-3]; transcriptomics [4]; proteomics [5][6][7][8][9]; metabolomics [10,11], and nutrigenomics [12].The objective of this topic is to offer a platform for marine biological scientists to present recent advances in the discovery and development of omics in marine biotechnology, providing a large-scale, holistic approach to understanding life in encapsulated "omes". In this special topic, several genomes, including major histocompatibility complex genes [2], phytochrome genes [3] and immune-and antiviral-related genes [4], have been systematically investigated based on functional genomic studies, providing targets for further structural and functional analyses.…”
mentioning
confidence: 99%
“…This topic contains 12 papers produced by research groups from China, Germany, and Korea. To help readers, we have arranged the papers according to their research topics: genomics [1-3]; transcriptomics [4]; proteomics [5][6][7][8][9]; metabolomics [10,11], and nutrigenomics [12].…”
mentioning
confidence: 99%